Simple views on condensed matter - Gennes, Pierre-Gilles de (Series in modern condensed matter physics, 2003)
This volume is a selection of invaluable papers by P-G de Gennes — 1991 Nobel Prize winner in Physics — which have had a long-lasting impact on our understanding of condensed matter. Important ideas on polymers, liquid crystals and interfaces are described. The author has added some afterthoughts to the main papers (explaining their successes or weaknesses), and some current views on each special problem. The text is simple and easy to read.